Electronic fetal monitoring in the twenty-first century: Language, logic and Lewis Carroll. (September 2021) - Sartwelle, Thomas P; Johnston, James C; Arda, Berna; Zebenigus, Mehila
The Alice Books, full of illogical thoughts, words, and contradictions, were unrivaled entertainment until the publication of the medical literature promoting electronic fetal monitoring (EFM) for every pregnancy. The modern-day EFM advocates acknowledge EFM's decades long failure but simultaneously recommend EFM use for lawsuit protection and because the profession has used EFM for every pregnancy for fifty years, therefore, it must be efficacious. These self-indulgent, illogical rationalizations ignore the half century of evidence-based scientific research proving that EFM is a complete failure as well as ignoring the fact that continued EFM use violates the fundamental principles of modern bioethics. This blind advocacy perpetuates four pernicious EFM harms occurring to mothers, babies, and the medical profession itself. This article sets out these four EFM harms with the goal of abolishing the misguided, illogical, contradictory, arguments used by the twenty-first century EFM Lewis Carroll mimics.